Association of Aromatase Inhibitors With Coronary Heart Disease in Women With Early Breast Cancer. (21st April 2014) - Seruga, B.; Zadnik, V.; Kuhar, C. Grasic; Marinko, T.; Cufer, T.; Zakotnik, B.; Zorman, D.; Ocana, A.; Amir, E.
Abstract : As compared to tamoxifen aromatase inhibitors (AIs) may increase the risk of heart disease. Here we explored the association between the use of AIs and coronary artery disease (CAD) in a population-based observational study. In a small and heterogeneous population of 74 women with early breast cancer who received adjuvant hormonal therapy and subsequently underwent cardiac angiography, AIs significantly increased the hazard for CAD (HR 3.23, 95% confidence intervals [CI] 1.26–8.25, p = .01) compared to tamoxifen. Our results suggest that therapy with AIs may increase the risk for CAD.